Physical education specialists’ professional training in the United States - Dereka Tеtiana (Continuing Professional Education: Theory and Practice, 2019)
The article analyzes the characteristics of educational standards in physical education in the USA. The areas of five US national sports orientated associations are characterized here. It is determined that the key features of the US highest education system are its decentralization, multicultural focus with maximum regard to the needs of American society, labor market and current trends in the field of pedagogical knowledge. The levels of the US highest education in professional training system within the field of physical culture and sports are characterized here. The author presents the educational programs of physical education specialists’ training in the USA highest education institutions. The features of universities’ applicants selection (future teachers) and criteria of educational reviling are given. The structure of education levels (bachelor, master, doctor) is analyzed here. This structure contributes to the principle of professional education continuity implementation. The professional pedagogical subjects unit of American universities is characterized. It is indicated that the key traits of multilevel training of physical education teachers in the US universities are the differentiation and individualization of learning within personal approach to teachers’ education, practical orientation of each course, variability of practical teaching methods within the activity approach, with emphasis on the formation of special pedagogical knowledge of the teacher based on the integration of acquired knowledge and skills from different disciplines blocks. Students are provided with knowledge of philosophical, theoretical, legal, psychological and sociological foundations of physical education.